Analysis of integrin turnover in fly myotendinous junctions. - Yuan, L.; Fairchild, M.J.; Perkins, A.D.; Tanentzapf, G. (Journal of Cell Science, 2010)
Transient (short-term) cell adhesion underlies dynamic processes such as cell migration, whereas stable (long-term) cell adhesion maintains tissue architecture. Ongoing adhesion complex turnover is essential for transient cell adhesion, but it is not known whether turnover is also required for maintenance of long-term adhesion. We used fluorescence recovery after photobleaching to analyze the dynamics of an integrin adhesion complex (IAC) in a model of long-term cell-ECM adhesion, myotendinous junctions (MTJs), in fly embryos and larvae. We found that the IAC undergoes turnover in MTJs and that this process is mediated by clathrin-dependent endocytosis. Moreover, the small GTPase Rab5 can regulate the proportion of IAC components that undergo turnover. Also, altering Rab5 activity weakened MTJs, resulting in muscle defects. In addition, growth of MTJs was concomitant with a decrease in the proportion of IAC components undergoing turnover. We propose that IAC turnover is tightly regulated in long-term cell-ECM adhesions to allow normal tissue growth and maintenance.